2006
DOI: 10.1016/j.jacc.2006.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind Comparison of Sirolimus-Eluting Stent Versus Bare-Metal Stent Implantation in Diseased Saphenous Vein Grafts

Abstract: Sirolimus-eluting stents significantly reduce late loss in SVG as opposed to BMS. This is associated with a reduction in restenosis rate and repeated target lesion and vessel revascularization procedures. (The RRISC Study; http://clinicaltrials.gov/ct/show; NCT00263263).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
8

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(87 citation statements)
references
References 47 publications
3
69
0
8
Order By: Relevance
“…23 However, late follow-up data from the same trial at 48 months, reported in the DELAYED RRISC trial, demonstrated an increase in mortality for patients who underwent SVG intervention with sirolimuseluting stents compared to BMSs (29% vs 0%, respectively; p Ͻ0.001). 15 Although this appears to be a concerning finding from this small randomized trial (n ϭ 75), no other study has suggested increased mortality with DESs in SVG disease at long-term follow-up.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…23 However, late follow-up data from the same trial at 48 months, reported in the DELAYED RRISC trial, demonstrated an increase in mortality for patients who underwent SVG intervention with sirolimuseluting stents compared to BMSs (29% vs 0%, respectively; p Ͻ0.001). 15 Although this appears to be a concerning finding from this small randomized trial (n ϭ 75), no other study has suggested increased mortality with DESs in SVG disease at long-term follow-up.…”
Section: Discussionmentioning
confidence: 94%
“…The results of the Death and Events at Long-term follow-up AnalYsis: Extended Duration of the Reduction of restenosis in saphenous vein grafts with Cypher stent (DELAYED RRISC) trial 15 were used because the length of follow-up was longer than the follow-up in the Reduction of Restenosis In Saphenous vein grafts with Cypher sirolimus-eluting stent (RRISC) trial. 23 The primary end point was TVR, which was defined as subsequent percutaneous or surgical revascularization of the Data are presented as DES/BMS. DES ϭ drug-eluting stent; DEP ϭ distal embolic protection; DM ϭ diabetes mellitus; EF ϭ ejection fraction; GP ϭ glycoprotein; NR ϭ not reported; PCI ϭ percutaneous coronary intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the growing evidence of the benefits of DES in several subsets of lesions [4][5][6][7][8][9][10] and patients [11][12][13][14], very few data are available on the benefit of DES in saphenous vein grafts (SVG) over the long term. A recent small prospective randomized trial between the Sirolimus-eluting (SES) stent and BMS [15] reported a significant reduction of late lumen loss, restenosis and repeat target lesion and vessel revascularization at 6 months with SES. Current available registries of DES in SVG [16][17][18][19][20][21] report inconsistent results and they are limited by small enrollments and short-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, meta-analyses 4,5 and long-term followup data 6,7 demonstrated that DES improved morbidity but did not reduce mortality (compared with bare metal stents; BMS). Newer generation DES may solve the problems encountered with first-generation DES.…”
mentioning
confidence: 99%